Aśvaghosha kī krtiyoṃ meṃ citrita Bhāratīya saṃskrti - Nasarīna, Kiśvara Jabīṃ (Hindustānī Ekeḍemī, 1983)
Study of Indic civilization as presented in the poems of Aśvaghoṣa, classical Sanskrit poet and Buddhist philosopher.